Pengaruh Rasio Earning per Share (EPS), Return on Equity (ROE) danNet Profit Margin (NPM) pada Harga Saham (Studi pada Saham Perusahaan yang Tercatat dalam IDX30 di BEI Periode 2014-2017) - Yani Monalisa (Jurnal Akuntansi, 2019)
This study aims toanalyze the effect of earning per share (EPS), return on equity (ROE) and net profit margin (NPM) on stock price, whichare listed active in IDX30 in BEI Period 2014-2017. Data analyzed using multiple regression analysis, t-Test and F-Test with significance level of 5%. Data have been processed by using SPSS Ver. 23 for windows. The results showed partial EPS, ROE and NPM influence on stock price and three ratios simultaneously influence stock price. Keywords: EPS, ROE, NPM, Stock Price and IDX30